The Culturalization of Politics, Religion and Cultural Wars: The Case of Turkey and the Turkish Cypriot Community - Nikos Moudouros (Religions)
This article examines the transformation of religion into a structural part of cultural war, as well as the broader process of the culturalization of politics, as a hegemonic strategy. Within this specific context, the article describes the evolution of cultural war in Turkey and how it is transferred in the context of the Turkish Cypriot community. The first part of the article contains a general analysis of the process of the culturalization of politics and its connection with the question of hegemony. The second part focuses on the case of Turkey and, more specifically, on how the Turkish right has instrumentalized religion in cultural war. It places the AKP within the aforementioned context and describes the importance it has placed on the strengthening of religion in the educational structures of the country. The last part of the article focuses on the evolution of cultural war between Turkey and the Turkish Cypriot community. It examines the key views of the AKP on the transformation of Turkish Cypriot collective identity and the role religion should play. It also examines the reaction of sections of the Turkish Cypriot community, mainly originating from the historical dimension of Turkish Cypriot secularism.